Bank Accounts for Public Finance Agencies Income - Paweł Lenio (Prawo Budżetowe Państwa i Samorządu)
The subject of this paper are bank accounts for public finance agencies income. The article describes characteristics of accounts for all three kinds of agencies: government and municipal units working in regards to statue of education and units with headquarters in foreign countries. The author presents a detailed directory of income for particular accounts and the allocation of said income. This paper also deals with the optionality of those dedicated bank accounts and the competence for erecting them. In a smaller scope there are presented the controversies of establishing bank accounts for public finance agencies income in the past, before the current statue of public finance.